Delamination analysis of carbon fibre reinforced laminates: evaluation of a special step drill - Marques, A. T. (2014)
Drilling of carbon fibre/epoxy laminates is usually carried out using standard drills. However, it is necessary to adapt the processes and/or tooling as the risk of delamination, or other damages, is high. These problems can affect mechanical properties of produced parts, therefore, lower reliability. In this paper, four different drills – three commercial and a special step (prototype) – are compared in terms of thrust force during drilling and delamination. In order to evaluate damage, enhanced radiography is applied. The resulting images were then computational processed using a previously developed image processing and analysis platform. Results show that the prototype drill had encouraging results in terms of maximum thrust force and delamination reduction. Furthermore, it is possible to state that a correct choice of drill geometry, particularly the use of a pilot hole, a conservative cutting speed – 53 m/min – and a low feed rate – 0.025 mm/rev – can help to prevent delamination.